Clinical and Echocardiographic Characteristics and Cardiovascular Outcomes According to Diabetes Status in Patients With Heart Failure and Preserved Ejection Fraction: A Report From the I-Preserve Trial (Irbesartan in Heart Failure With Preserved Ejection Fraction). Issue 8 (21st February 2017) - Kristensen, Søren L.; Mogensen, Ulrik M.; Jhund, Pardeep S.; Petrie, Mark C.; Preiss, David; Win, Sithu; Køber, Lars; McKelvie, Robert S.; Zile, Michael R.; Anand, Inder S.; Komajda, Michel; Gottdiener, John S.; et al.
Abstract : Background: In patients with heart failure and preserved ejection fraction, little is known about the characteristics of, and outcomes in, those with and without diabetes mellitus. Methods: We examined clinical and echocardiographic characteristics and outcomes in the I-Preserve trial (Irbesartan in Heart Failure With Preserved Ejection Fraction) according to history of diabetes mellitus. Cox regression models were used to estimate hazard ratios for cardiovascular outcomes adjusted for known predictors, including age, sex, natriuretic peptides, and comorbidity. Echocardiographic data were available in 745 patients and were additionally adjusted for in supplementary analyses. Results: Overall, 1134 of 4128 patients (27%) had diabetes mellitus. Compared with those without diabetes mellitus, they were more likely to have a history of myocardial infarction (28% versus 22%), higher body mass index (31 versus 29 kg/m 2 ), worse Minnesota Living With Heart Failure score (48 versus 40), higher median N-terminal pro-B-type natriuretic peptide concentration (403 versus 320 pg/mL; all P <0.01), more signs of congestion, but no significant difference in left ventricular ejection fraction. Patients with diabetes mellitus had a greater left ventricular mass and left atrial area than patients without diabetes mellitus. Doppler E-wave velocity (86 versus 76 cm/s; P <0.0001) and the E/e' ratio (11.7 versus 10.4; P =0.010) were higher in patients with diabetes mellitus. Over a median follow-up of 4.1 years, cardiovascular death or heart failure hospitalization occurred in 34% of patients with diabetes mellitus versus 22% of those without diabetes mellitus (adjusted hazard ratio, 1.75; 95% confidence interval, 1.49–2.05), and 28% versus 19% of patients with and without diabetes mellitus died (adjusted hazard ratio, 1.59; confidence interval, 1.33–1.91). Conclusions: In heart failure with preserved ejection fraction, patients with diabetes mellitus have more signs of congestion, worse quality of life, higher N-terminal pro-B-type natriuretic peptide levels, and a poorer prognosis. They also display greater structural and functional echocardiographic abnormalities. Further investigation is needed to determine the mediators of the adverse impact of diabetes mellitus on outcomes in heart failure with preserved ejection fraction and whether they are modifiable. Clinical Trial Registration: URL:http://www.clinicaltrials.gov . Unique identifier: NCT00095238. Abstract : Supplemental Digital Content is available in the text.